On the role of topical drugs in the treatment of acute otitis media in children - D. A. Tulupov; E. P. Karpova; O. G. Naumov (Медицинский совет, 2019)
The article presents an overview of modern approaches to diagnosis and treatment of acute otitis media in children. On the basis of the existing clinical recommendations the indications for systemic antibacterial therapy and tympanocentesis are listed, the algorithm of antibacterial therapy accepted in Russia is described. The role of various drugs in the form of ear drops for local treatment of acute otitis media in children is considered separately. One clinical case is presented, illustrating the capabilities of local anesthetics in the treatment of acute otitis media.